The Night Gardener - Auxier, Jonathan (Amulet Books, 2014)
Irish orphans Molly, fourteen, and Kip, ten, travel to England to work as servants in a crumbling manor house where nothing is quite what it seems to be, and soon the siblings are confronted by a mysterious stranger and secrets of the cursed house.